Semiotics of Islamic Law: Symbolic Interpretation of Islamic Legal Text of Ibn ‘Arabi - Junaidi, Ahmad; Waeno, Muhammadaree (Millati: Journal of Islamic Studies and Humanities, 2024)
Many Muslims are trapped in carrying out formal rituals of the Sharia without understanding and appreciating the nature and essence of what it contains. Many underestimate it and even dare to abandon the formal rituals of the Sharia because the formal ritual practice of the Sharia is no longer needed once its nature and essence are understood. These two extreme points have always adorned the face of Muslims, from early times to the most recent modern times. Ibn ‘Arabi was a Sufi figure from Andalusia, Spain, who paid great attention to the issue of the dichotomy between Sharia and nature. The effort he made was to give symbolic meaning to Islamic legal texts. Aimed at a deeper understanding of the Koran and by the invitation to preach to Allah through wise methods (al-baṣīrah). This effort aims to balance al-kashf and the practice of worship both in general and in detail. The important aim of this symbolic meaning is ultimately for one’s safety (bi najāti nafsihi) in addition to preaching the teachings of Islam and the teachings of Sufism in depth. His intellectual chain was then continued by his students and then developed to this day and has an influence on the work and ideas of the next generation.